Development of interregional cooperation in the context of еuropean integration - Serebryak, K.; Belousova, L.; Zablodska, D. (Baltic International Academy, 2019)
Стаття присвячена розробленню теоретичних засад та практичних рекомендацій щодо розвитку міжрегіонального співробітництва в умовах євроінтеграції на засадах його концептуалізації та обґрунтуванні напрямів розширення співпраці регіонів України з країнами ЄС у реальному секторі економіки. Визначено інструменти світового сприяння розвитку регіонального (міжрегіонального) співробітництва в Україні. // The article is devoted to the development of theoretical principles and practical recommendations for the development of interregional cooperation in the context of European integration on the basis of its conceptualization and justification of expanding cooperation between Ukrainian regions and EU countries in the real sector of the economy. The tools of world assistance to the development of regional (interregional) cooperation in Ukraine are determined.
Keywords: європейська інтеграція; концепція; міжрегіональне співробітництво; регіони; European integration; concept; interregional cooperation; regions